Studies on Phosphatase Enzyme Activity of Pseudomonas fluorescens Isolates of Jatropha curcas L. - Shukla, Rekha; , Jamaluddin; Pandey, A. K. (Indian Forester, 2010)
Phosphate solubilizingbacteria are known to play a major role in the solubilization of unavailable forms of soil phosphorus and uptake its native and applied forms. A total of 17 different Pseudomonas flourescens isolates recovered from rhizosphere and J.curcas, planted in different localities, were evaluated for their phosphatase activity in in vitro and in vivo conditions. Isolates viz., P#10, P#l1 and P#02 revealed maximum phosphatase enzyme activity and influence the maximum growth and therefore can be used as bioinoculant in nursery and field trials for better production of J.curcas.